Functional results of surgical treatment with elastic nails for closed displaced forearm diaphyseal fractures in children (8-15 years) - يوسف علي (Latakia University Journal -Medical Sciences Series, 2024)
Objective of the study: To study the functional results in treating this type of common fracture using elastic nails with the aim of achieving healing, restoring function, and reducing complications. Materials and methods: The study was conducted on 20 children who were admitted to Tishreen University Hospital during the years 2022-2023 and who underwent surgical treatment using flexible Intramedullary nails after clinical and radiological evaluation. Patients were followed up clinically and radiographically at postoperative intervals and clinical and radiological re-evaluation. Results: The study sample included 20 patients, with a predominance of males, 15 children versus 5 females, and the ages ranged between 8-15 years. The reason was exposure to sports injuries and car accidents. Patients were followed clinically and radiographically after surgery. The study reached good and important results in restoring forearm function and healing fractures. Conclusion: This study concluded the importance of using flexible Intramedullary nails in treating this type of fracture and obtaining positive results while reducing complications.